Implementasi Program Mahasiswa Peduli Stunting BKKBN Banten di Kelurahan Kilasah Kota Serang Berdasarkan Perpres No. 72 Tahun 2021 - Muanah Muanah; H.E Rakhmat Jazuli; Ahmad Rayhan (Pemuliaan Keadilan, 2025)
The Student Care for Stunting Program is an innovation by BKKBN in collaboration with universities to support the acceleration of stunting reduction through real work lectures or other community service activities. This program is part of the government's efforts to achieve the target of reducing the stunting rate to 14% by 2024, as mandated by the President. This study identifies the implementation of the BKKBN Student Program for Stunting Prevention in Banten Province, specifically in Kilasah Village, as well as the challenges faced in its implementation. The study employs government action theory and the welfare state theory using a legal-empirical method through a qualitative field approach. Data was collected through literature reviews and interviews, analyzed descriptively and analytically. The results show that the program's implementation has included 15 outreach and mentoring activities. Fifteen adolescents received reproductive health education, 21 pregnant and breastfeeding mothers received nutrition and pregnancy health counseling, and 20 prospective couples participated in socialization on healthy pregnancy planning and the use of the Elsimil application. Growth monitoring was conducted at nine Posyandu centers with a total of 60 infants, and 37 cases of infants indicated as stunted were identified. Challenges faced include the absence of specific regulations regarding the program and resistance from the target groups, particularly adolescents and prospective brides and grooms who struggled to understand the Elsimil app. In conclusion, the program has a positive impact on efforts to accelerate stunting reduction, although improvements are still needed in terms of regulations, coordination, and culture-based education.